Effect of psychological first aid training for fellows on resident burnout and distress in the intensive care unit - Haley Belt; Carol S. North; Traci N. Adams (PLoS ONE, 2026)
Background Burnout is a common problem among medical trainees and can result in medical errors and intention to leave practice. Psychological first aid (PFA) is a form of mental health assistance provided after critical incidents with the goal of reducing distress and re-establishing functioning; the application of PFA to medical trainees has been suggested but studies are lacking. Methods Pulmonary and critical care medicine fellows were given a 2-hour PFA training. Fellows were administered a survey immediately after training and again 3 months later. The effect of fellow PFA training on burnout and distress scores among medical residents supervised by pulmonary fellows was measured during medical intensive care unit (ICU) rotations and compared to ICU medical resident burnout and distress scores prior to PFA training. Results Of the 11 fellows who completed the survey, 91% had a positive or extremely positive impression of the training. Six fellows noted a change of practice as a result of the training on the 3-month follow up survey. Resident burnout scores at the end of an ICU rotation were lower in the months following the PFA training compared to those at the end of an ICU rotation before the PFA training. Conclusions This study demonstrates that bringing PFA training to trainees is both feasible and well-received and suggests that PFA training may impact trainees in settings that are high risk for burnout. The PFA training in this study may serve as a model for further attempts to educate healthcare workers in PFA.